An updated and annotated checklist of the Tylenchulidae (Nematoda: Criconematoidea) of Iran - Ghaderi, Reza; Karegar, Akbar; Miraeiz, Esmaeil; Hesar, Abbas Mokaram (Zootaxa, 2019)
The list of plant parasitic nematodes of the family Tylenchulidae, collected from Iran, is updated. Forty-one species belonging to five genera and three subfamilies are included in the list. Data for seven species of Paratylenchus are added, of which two species—P. perminimus and P. salubris—are new records for the Iranian nematofauna. The list of species, further information on their morphometrics, references to full or partial descriptions, associated plants, geographical distribution and some taxonomic remarks are provided. More detailed studies on some doubtful populations are added. Information on the taxonomic position of species in different classification schemes, as well as the preferences of some species for certain climatic conditions or ecological niches is provided.